Application of Foot Massage in Reducing Pain After Cesarean Section Surgery in Postpartum Women - Ryaswati, Luthfi; Nurrohmah, Anjar (Yayasan Inspirasi El Burhani, 2023)
Introduction: Sectio Caesarea (SC) is a way of delivering a fetus by making an incision in the uterine wall through the front wall of the abdomen. SC delivery has an impact on both mother and baby. Post-SC mothers will experience pain. The pain usually appears 4-6 hours after the delivery process is complete. Foot massage is one of the massage measures developed and implemented in hospitals for non-pharmacological pain management. Objective: Knowing the results of the application of foot massage techniques in reducing pain after cesarean section surgery in postpartum women. Methods: This application uses a descriptive case study method, with a total application sample of 2 respondents. This application was carried out for 2 days, with each day lasting 20 minutes. Results: The results of the application showed that both respondents before and after being given foot massage decreased from the moderate to mild category. Conclusion: There is an effect of foot massage on reducing pain after Sectio Caesarea surgery in postpartum women in the Cempaka Room of RSUD Dr. Soehadi Prijonegoro Sragen.